Determinants of financing in Indonesian Islamic banking - Pratami, Arifa; Roslan, Mohammad Nasrul Hakim; Ismail, Ismail (Economics, Finance, and Business Review, 2025)
This study aims to analyze the factors that affect the distribution of financing in Islamic commercial banks in Indonesia for the period 2015–2023 with quarterly panel data on 34 Islamic commercial banks. This study applies the dynamic panel regression method with the GMM system. The results show that market power, as measured by the Lerner Index, has a significant negative effect, indicating that a less competitive market structure is suppressing financing expansion. Internal factors such as profits and bank size have a positive effect, while capital adequacy reduces financing disbursement. In profit-sharing financing (PLS), risk-based variables such as NPF and profitability have a significant negative influence, while bank size and economic conditions have a positive effect. Non-profit sharing (Non-PLS) financing is more sensitive to operational efficiency, financing risks, and macroeconomic conditions. The COVID-19 pandemic has been proven to reduce financing in all categories, especially PLS, which have higher risks. Overall, the results of the study confirm that the financing behavior of Islamic banks in Indonesia is influenced by a combination of market dynamics, the fundamental strength of banks, risk quality, and macroeconomic conditions, with significant differences between profit-sharing and non-profit-based financing.